Eﬀects of the association of physical exercises and self-drainage in the treatment of cellulite - Balsamo, Anna; Panero, Francesca; de Morais Carreiro, Eneida; Castellini, Riccardo; Castellini, Martina; Martins de Andrade, Ana Laura; Froes Meyer, Patrícia (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2025)
Introduction. Cellulite is a descriptive term used to characterise the topographic alteration of the skin, with a high prevalence in females. Manual lymphatic drainage (MLD) stands out as a technique that, when used alone or associated with other tech-niques such as exercises and/or physical activities, improves the general appearance of this condition. To evaluate the eﬀects of self-MLD associated with supervised kinetic exercises in the treatment of cellulite and improvement in the quality of life of patients.Methods. We included 50 participants, randomly divided into two groups: a control group of only diet and an exercise and MLD group (EMG) with diet. The participants were evaluated using a questionnaire evaluating the quality of life (Celluqol), electrical bioimpedance, body anthropometric measurements, and satisfaction analysis with the questionnaire GAIS.Results. Signiﬁcant improvement was observed in the quality of life of the EMG, in addition to presenting a signiﬁcant reduction in %BF and analysed anthropometric measurements. In addition, evaluations regarding patient satisfaction showed signiﬁcant improvements in the EMG.Conclusions. Through the data presented, it is possible to conclude that the diet with caloric restriction associated with self-MLD promotes a signiﬁcant improvement in individuals with cellulite.
Keywords: lymphatic drainage; cellulite; exercise